MEMAKNAI TARI BARIS SUMBU DI PURA DESA SEMANIK, DESA PELAGA, PETANG, KABUPATEN BADUNG - Ida Ayu Gede Suryawati (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
Religion and art in Bali always appear to be mutually reinforcing one another. The religion gives taksu (spirit) to the arts, while the arts gives exotic nuance to the existence of religion in the society. Likewise the existence of Baris Sumbu Dance in Banjar Semanik Pelaga Petang Badung, with the attributes of sumbu, tipat, and bantal as the main means of staging. This paper analyzes the symbols used in the Baris Sumbu Dance. It is found that the tipat, bantal are the symbols of the‘wedding of purusa and pradhana’ to produce a new life that gives welfare to the society.